Encyclopedia of Drug Metabolism and Interactions 2012
DOI: 10.1002/9780470921920.edm025
|View full text |Cite
|
Sign up to set email alerts
|

ABCDrug Transporters and Their Impact on Drug Disposition/Drug Sensitivity and Resistance

Abstract: The “ATP‐binding cassette” superfamily of proteins comprises 49 members, each possessing evolutionarily conserved sequence motifs that lie in the proteins nucleotide (ATP) binding domain. Each member is further classified into seven subclasses (A–G). Most ABC proteins function as membrane‐bound efflux pumps, transporting various small‐molecule substrates from the cytoplasm to the extracellular space; however, there are some exceptions (ABCE and ABCF). A vast array of drugs used in the treatment of diseases suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 238 publications
0
2
0
Order By: Relevance
“…Previous clinical studies have shown that estramustine is sequestered and effluxed by ABCA2 in resistant ovarian carcinoma 13,37. Docking analysis performed on a predicted model of ABCA2 suggested that ABCA2 is able to bind estramustine (docking grid energy equal to −42.395 kcal/mol) (data not shown).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous clinical studies have shown that estramustine is sequestered and effluxed by ABCA2 in resistant ovarian carcinoma 13,37. Docking analysis performed on a predicted model of ABCA2 suggested that ABCA2 is able to bind estramustine (docking grid energy equal to −42.395 kcal/mol) (data not shown).…”
Section: Resultsmentioning
confidence: 80%
“…Previous clinical studies have shown that estramustine is sequestered and effluxed by ABCA2 in resistant ovarian carcinoma. 13 , 37 Docking analysis performed on a predicted model of ABCA2 suggested that ABCA2 is able to bind estramustine (docking grid energy equal to −42.395 kcal/mol) (data not shown). The overlap between the ABCA2 and ABCA3 models obtained by Phyre2 outlined the presence of similar domains (ie, transmembrane helixes and nucleotide-binding domains) ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%